2018
DOI: 10.18632/oncotarget.23886
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Immuno-PET of CD138 and PET imaging with 64CuCl2 and 18F-FDG in a preclinical syngeneic model of multiple myeloma

Abstract: PurposeAlthough recent data from the literature suggest that PET imaging with [18]-Fluorodeoxyglucose (18F-FDG) is a promising technique in multiple myeloma (MM), the development of other radiopharmaceuticals seems relevant. CD138 is currently used as a standard marker in many laboratories for the identification and purification of myeloma cells, and could be used in phenotype tumor imaging. In this study, we evaluated a 64Cu-labeled anti-CD138 murine antibody (64Cu-TE2A-9E7.4) and a metabolic tracer (64CuCl2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 38 publications
2
38
0
Order By: Relevance
“…However, preclinical therapies were conducted on a xenograft model which is not suitable for assessing toxicities related to physiological uptake. Therefore, building on our previous promising results obtained with bismuth-213 or during the imaging of MM with copper-64, we have once more favored CD138 as a target antigen [21][22][23]49]. CD138 or syndecan-1 has long been considered as the most reliable marker of MM and is still widely used for the diagnosis of MM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, preclinical therapies were conducted on a xenograft model which is not suitable for assessing toxicities related to physiological uptake. Therefore, building on our previous promising results obtained with bismuth-213 or during the imaging of MM with copper-64, we have once more favored CD138 as a target antigen [21][22][23]49]. CD138 or syndecan-1 has long been considered as the most reliable marker of MM and is still widely used for the diagnosis of MM.…”
Section: Discussionmentioning
confidence: 99%
“…Its specificity has been studied by ELSA assay, cytometry [22] and by immunohistochemistry on skin tissue, spleen tissue, liver tissue and lung tissue. This antibody has also been used with PET imaging to detect MM subcutaneous and intramedular lesions [23,24].…”
Section: Anti-cd138 Antibody 211 At Radiolabeling Immunoreactivity mentioning
confidence: 99%
“…The used antiCD138 mAb was the 9E7.4 mAb, whose characterisation was ensured within our team as previously described [109]. Coupling with TE1PA chelator and radiolabelling with 64Copper was carried out following our standard procedure and as previously reported in recent works [95,113].…”
Section: Discussionmentioning
confidence: 99%
“…Labeled antibodies may be used to detect cells in vivo by SPECT, PET, or NIR fluorescence. They have mainly been used for tumor diagnosis, staging or tumor response monitoring (54). It has been reported that labeled antibodies allow the tracking of T cells in vivo (55).…”
Section: Indirect Methods: Labeled Antibodies and Tracersmentioning
confidence: 99%